Tea Tree Oil Prevents Mastitis-Associated Inflammation in Lipopolysaccharide-Stimulated Bovine Mammary Epithelial Cells - Chen, Zhi; Zhang, Yi; Zhou, Jingpeng; Lu, Lu; Wang, Xiaolong; Liang, Yusheng; Loor, Juan J.; Gou, Deming; Xu, Huifen; Yang, Zhangping (Frontiers in Veterinary Science, 2020)
The main purpose of this study was to explore the effect of tea tree oil (TTO) on lipopolysaccharide (LPS)-induced mastitis model using isolated bovine mammary epithelial cells (BMEC). This mastitis model was used to determine cellular responses to TTO and LPS on cellular cytotoxicity (Cell Counting Kit 8, flow cytometry), mRNA abundance and cytokine production. High-throughput sequencing was used to select candidate genes, followed by functional evaluation of those genes. In the first experiment, LPS at a concentration of 200 μg/mL reduced cell proliferation, induced apoptosis and upregulated protein concentrations of tumor necrosis factor-α (TNF-α), interleukin 6 (IL-6) and signal transducer and activator of transcription 1 (STAT1). Addition of TTO led to reduced cellular apoptosis along with downregulated protein concentrations of nuclear factor kappa B, mitogen-activated protein kinase 4 (MAPK4) and caspase-3. In the second experiment, BMEC challenged with LPS had a total of 1270 differentially expressed genes of which 787 were upregulated and 483 were downregulated. Differentially expressed genes included TNF-α, IL6, STAT1, and MAPK4. Overall, results showed that TTO (at least in vitro) has a protective effect against LPS-induced mastitis. Further in vivo research should be performed to determine strategies for using TTO for prevention and treatment of mastitis and improvement of milk quality.